Validation of a Therapeutic Intervention Scoring System (TISS-28) in critically ill children - Ana Vivanco-Allende; Corsino Rey; Andrés Concha; Pablo Martínez-Camblor; Alberto Medina; Juan Mayordomo-Colunga (Elsevier, 2020)
Introduction: There are numerous scales in intensive care units that are used to quantify the severity of patients. Most of them are very useful, although sometimes laborious to complete, thus limiting their use in usual practice. One of these scales, the Therapeutic Intervention Scoring System (TISS-76), has been validated in adult and paediatric units. Its simplified and updated version, the Simplified Therapeutic Intervention Scoring System (TISS-28), has not yet been validated in paediatric units. The aim of this study is to validate TISS-28, in order to have a simple and rapid scale. Material and method: A prospective non-interventional observational study was conducted in a Paediatric Intensive Care Unit (PICU) of a university hospital. Data were collected from 935 consecutive patients admitted to the PICU over a 3-year period. These included the values of TISS-76 and TISS-28 during the first 4 days of admission and the subsequent outcome of the patients. Results: The mean values of TISS-76 and TISS-28 for the first day of admission were 18.27 and 18.02, respectively. Values were higher in patients who had sequelae or died (17.58 versus 27.23 and 37.44, respectively for TISS-76 (p < .01); and 17.51 versus 23.80 and 33.44, respectively for TISS-28 (p < .01).A very good correlation was found between TISS-76 and TISS-28, with Pearson correlation and intraclass correlation coefficients >0.9 (except for the 2nd day). The correlation equation for the overall 4 days was: TISS-76 = −1.74 + 1.05 × TISS-28. TISS-28 was able to explain 82.4% of variability of TISS-76. The area under the curve with a confidence interval (CI) of 95% for the first day was 0.80 (0.73-0.87) for TISS-76, and 0.76 (0.67-0.84) for TISS-28. Conclusions: On observing the results obtained, TISS-28 can replace TISS-76 in our PICU, without worsening the information provided. Being a reliable scale and easier to apply, its practical application could be useful. Resumen: Introducción: En el ámbito de los cuidados intensivos, existen numerosas escalas para cuantificar la gravedad de los pacientes. La mayoría de ellas son muy útiles, aunque en ocasiones laboriosas de completar, por lo que su implantación en la práctica habitual es escasa. Una de ellas es la escala de puntuación de intervenciones terapéuticas (TISS 76), que ha sido validada en unidades de adultos y pediátricas. Su versión simplificada y actualizada, la escala simplificada de puntuación de intervenciones terapéuticas (TISS 28), no ha sido validada en unidades pediátricas, siendo este el objetivo del estudio, con idea de disponer de una escala sencilla y rápida. Material y método: Estudio observacional prospectivo sin intervención, en la Unidad de Cuidados Intensivos Pediátricos (UCIP) de un hospital universitario. Se recogieron datos de 935 pacientes ingresados consecutivamente en la UCIP durante un periodo de 3 años, incluyendo los valores de TISS 76 y TISS 28 de todos durante los 4 primeros días de ingreso y la posterior evolución de los pacientes. Resultados: Los valores medios de TISS 76 y TISS 28 para el primer día de ingreso fueron de 18,27 y de 18,02, respectivamente, siendo más elevados en los pacientes con secuelas o que fallecían. Se encontró muy buena correlación entre la TISS 76 y la 28, con coeficiente de correlación de Pearson y de correlación intraclase >0,9 (excepto para el segundo día). La ecuación de correlación para los 4 días fue: TISS76 = −1,74 + 1,05 × TISS28. La TISS 28 fue capaz de explicar el 82,4% de la variabilidad de la TISS 76. El área bajo la curva con un intervalo de confianza del 95% para el primer día fue de 0,80 para la TISS 76 y de 0,76 para la TISS 28. Conclusiones: Con los resultados obtenidos, la TISS 28 puede reemplazar a la TISS 76 en nuestra UCIP, sin empeorar la información proporcionada. Siendo una escala fiable y más sencilla de aplicar, podría ser útil su aplicación práctica.